PENGARUH IKLIM ORGANISASI TERHADAP EFEKTIFITAS PELAYANAN PUBLIK DI KECAMATAN TALIABU UTARA KABUPATEN KEPULAUAN SULA - MAMO, AMBRON SIUS; Rumapea, Patar; Ruru, Joorie Marhaen (Sam Ratulangi University, 2015)
Abstract : Organizational knowledge is an important factor to explain the effectivenessas it relates to the organization’smorale employee. Bureaucratic organization’s impressed thegovernment has not been able to motivate emploe morale to improve the effectiveness of its workbecause of the critical diminsions of organizational climate has not been realized in accordancewith the needs and espectation of employes, and the suspeck is the of the causes have notmakximum service effectiveness.Inconnection with this matler,this study was to determine theeffect of organizational climate on the district government public service effectiveness TaliabuUtara north sula island.This research uses methods quantitative data source research respondents are as manyas 30 officer/employess government districts Taliabu Utara.Data collection technique usingquestionnaires and interviews quide.Techniquehelp with data analysis to test the hypothesissimple regressionanalysis and correlation simple/product moment.Data analysis showe : (1) variable regression coefficient effectiveness organizationclimate on public services is positive and the real significance level of 0,01 or 1%. (2) Thecorrelation coefficient and the power of organization climate variable determination of theeffectiveness of public services is high/close and rear to the significant level of or 1%.The conclusions suggested by the results of the study the effectiveness a public servantin the office distrct heard north Taliabu needs to be improved by improving the qualitydimensions of organizational climate can push high morale of employes such as:tskstructure,the relationship reward - penalties,communications within the organization ,thedevelopment of human resources mployee,the personal relationship between the atmospherewithin the organization,facilities and/support eguipment executing the task,and the safety andcomfort of the organization’s environment.Keywords:Organizational knowledge, public services effectiveness.